Analisis sifat fisis dan mekanis papan partikel limbah jagung berperekat kitosan sebagai kandidat material lantai bagasi mobil - Haikal Zaki Muttaqin; Kardiman; Lilik Astari (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
This research focused on examining the physical and mechanical characteristics of particleboard created from corn stalk byproducts and chitosan adhesive, serving as an eco-friendly alternative material, particularly for vehicle trunk flooring uses. The approach to the research included creating particleboard with different concentrations of chitosan adhesive at 20%, 25%, and 30%. The physical characteristics (moisture content, density, water absorption, and thickness swelling) and mechanical characteristics Modulus of Elasticity and Modulus of Rupture were subsequently assessed following the JIS A 5908:2003 standard. The findings indicated that the density values of the particleboard for all variations conformed to the standard, whereas the moisture content complied with the standard only at concentrations of 20% and 25%. Water absorption and thickness swelling remained quite elevated across all treatments, suggesting poor moisture resistance because of the material's hygroscopic characteristics. The maximum MOE value was reached at a concentration of 25%, whereas the peak MOR value was found at a concentration of 20%. Overall, raising the adhesive concentration doesn't consistently enhance mechanical properties, and there exists an ideal value at specific compositions.